Antitrust Standards and Railway Freight Pricing: New Round in an Old Debate - Spychalski, John C. (American Economic Review, 1981)
Collective ratemaking has been practiced in various forms by American railway firms for more than a century. Its emergence antedated passage of the Sherman Act, and its survival despite both that legislation and subsequent federal and state antitrust laws stands out as a unique phenomenon in the annals of social control of business. Major challenges to collective railway ratemaking's continuance have occurred at three different periods. The most recent began with enactment of the Railroad Revitalization and Regulatory Reform Act of 1976 (4R Act), which narrowed the scope of antitrust immunity that had been accorded to rate bureau-based pricing by the Reed-Bulwinkle Act of 1948. Foremost among the 4R Act's changes in immunity were the prohibition of 1) collective determination of particular rates on single line movements, and 2) collective pricing of interline movements by railways which cannot practicably participate in such movements. Interpretation of the 4R Act's antitrust immunity provisions, to delimit their application, occupied a four-year proceeding in which the ICC, in a decision served August 13, 1980, issued a relatively narrow grant of immunity. The ICC also declared that the 4R Act prohibited discussion, as well as voting, on single line rates. In addition, it initiated a move toward elimination of antitrust immunity for collectively determined general rate increases and decreases, and broad changes in tariff conditions on single line traffic-despite a 4R Act provision that the prohibition on single line rate voting and the restriction on jointline rate voting shall not apply to such general rate or broad tariff changes. The ICC, in essence, took the view that intramodal railway rate competition, governed largely by antitrust standards, is workable. The ICC's decision imposes a standard of commercial behavior upon railways which, to the limited extent that it ever existed, was last seen in the nineteenth century. This marked departure from ingrained practice poses the question of whether it holds perceptible potential for improving efficiency in both transport and related sectors, as its proponents envisage. Scrutiny of conditions pertaining to this question, and to prospective consequences of the ICC's decision, occupies the remainder of the paper. Doing so requires the review of some very old but oft-slighted economic and institutional traits of rail transport.